2014
DOI: 10.1016/j.meegid.2014.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Microsatellite Typing reveals intra-focal genetic diversity among strains of Leishmania tropica in Chichaoua Province, Morocco

Abstract: In Morocco, cutaneous leishmaniasis (CL) caused by Leishmania (L.) tropica is a major public health threat. Strains of this species have been shown to display considerable serological, biochemical, molecular biological and genetic heterogeneity; and Multilocus Enzyme Electrophoresis (MLEE), has shown that in many countries including Morocco heterogenic variants of L. tropica can co-exist in single geographical foci. Here, the microsatellite profiles discerned by MLMT of nine Moroccan strains of L. tropica isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…tropica strains from different regions revealed that two main parasite populations exist in Turkey. Isolates from Şanlıurfa created a unique subpopulation and all Turkish isolates were clustered in a different population, which differs from Moroccan, but correlates with previous isolates from Israel and Palestine [28]. The MLMT data of the isolates clustered in Şanlıurfa population correlate with findings of previous study and noted to be the major L .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…tropica strains from different regions revealed that two main parasite populations exist in Turkey. Isolates from Şanlıurfa created a unique subpopulation and all Turkish isolates were clustered in a different population, which differs from Moroccan, but correlates with previous isolates from Israel and Palestine [28]. The MLMT data of the isolates clustered in Şanlıurfa population correlate with findings of previous study and noted to be the major L .…”
Section: Discussionsupporting
confidence: 81%
“…The possible reason for this kind of minor changes in microsatellite markers may be the immune status and capability of the patients. Additionally, it can be due to the clonal isolation of the parasite by culturing as previously reported [28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not further investigate the population structure of this species in Tataouine because of the reduced sample size and low level of genetic diversity, Despite the low level of genetic diversity in each species, the marked differentiation between L.major and L.killicki allowed us to explore patterns of hybridization between the two specie. Furthermore, since the microsatellites are co-dominant and generally neutral markers [52], they have been widely used to study genetic exchange within many organisms [53][54][55] of which Leishmania at both intra and interspecific level (between L. (Viannia) braziliensis and L. (Viannia) guyanensis [17]; between L.braziliensis and L. peruviana [23]; between L.guyanensis and L.panamensis [56]; between MON-1 and MON-24-80 of L. infantum [29,57]; between MON-1 and non MON-1 of L.infantum [58]; within L.tropica [59,60]; within L. donovani [31]. In our sample, neither the raw data nor the phenetic analysis suggests the occurrence of interspecific genetic exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite profiles previously described for 145 strains by Schwenkenbecher et al, 14 and Krayter et al 31,32 were included for comparison (Table 1, Supplemental Table 1). The GT4 locus was only used for the isolates typed at LSHTM whereas 27GTG was not used by Schwenkenbecher et al 14 Data for two loci, GT4 and 27GTG, were not available for all isolates in the extended set and were treated as missing data in those cases.…”
Section: Methodsmentioning
confidence: 99%